Marhaenism: A Case Study of Post-Reformation GMNI’s Performance and Development as a Cadre - Yintrosius Bena (International Journal Labs, 2022)
This study illustrates the progress and dynamics of GMNI as a cadre organization after the 1998-2018 reform. The research conducted was focused in 2005. To study this phenomenon researchers through several stages of research, the interview stage is considered capable and can find out the main problem to be investigated. This researcher focuses on the impact arising from the influence of GMNI for a policy. The theoretical framework used is ideology, Marhaenism, the concept of social organization, and the concept of functions of student organizations. The research method was carried out qualitatively and using descriptive research. In data collection used interviews, documentation, while for qualitative data analysis based on the use of complete and in-depth information in interpreting non-quantitative data. Based on research it can be seen that when organizational leaders at the national level experience stagnation to have a serious impact on the existence of the organization, although the activities of the socio-political movement in the region can slightly cover the obstacles faced by GMNI at the national level. The strengthening of the authoritarian rule of the New Order placed GMNI in two choices: Resigning in the sense of organizational disbandment so that its members were more focused on subjective issues, as students, or against all injustice practices of the authorities. When resisting, the actualization of the movement will be formulated in such a way in various forms of the anti status quo movement as an anti - Neo Colonialism Imperialism movement, ranging from study groups to radical movements.